The effectiveness of the Models of Assyria’s educational design in learning some of the motor abilities and basic skills of offensive basketball for the class of the fifth primary - Ali Dawood, Rafid (International Journal of Psychosocial Rehabilitation, 2020)
The current study aimed to identify the effectiveness of the Ashur model of educational design in learning some motor abilities and basic offensive skills in basketball for fifth-grade students and the moral differences between the experimental and control groups in the post-test in learning some motor abilities and basic offensive skills in basketball with basketball . The researcher used the experimental method for its suitability to the nature of the research, and the research sample included (40) students from the fifth grade of primary school in Noor Al Shams Primary School for the academic year 2019-2020, with (15) students for the experimental group and (15) students for the control group. in motor abilities and skills essential offensive of influential basketball, the researcher relied on Hynek and Molinda Russell designed the model, which is known as the model ASSURE In 1982, in order to design lessons, a researcher used statistical software (SPSS) for data processing, and the study concluded that there is a significant effect, not the Assyrian model of educational design, in learning some motor abilities and basic offensive skills in basketball for fifth-grade students.